2020
DOI: 10.1158/1535-7163.mct-19-0890
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific PEGylation of Anti-Mesothelin Recombinant Immunotoxins Increases Half-life and Antitumor Activity

Abstract: Recombinant immunotoxins (RIT) are chimeric proteins containing an Fv that binds to tumor cells, fused to a fragment of Pseudomonas exotoxin (PE) that kills the cell. Their efficacy is limited by their short half-life in the circulation. Chemical modification with polyethylene glycol (PEG) is a well-established method to extend the half-lives of biologics. Our goal was to engineer RITs with an increase in half-life and high cytotoxic activity. We introduced single cysteines at different locations in five anti-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Taken together, enhancement of LMB-100 efficacy is dependent not only on the selected chemotherapeutics but also on the type of cancer itself. None of the above studies could clearly define the mechanisms behind the observed synergistic effects, though further mechanistic and pharmacokinetic studies are underway ( 136 , 137 ).…”
Section: Pseudomonas Exotoxin Amentioning
confidence: 99%
“…Taken together, enhancement of LMB-100 efficacy is dependent not only on the selected chemotherapeutics but also on the type of cancer itself. None of the above studies could clearly define the mechanisms behind the observed synergistic effects, though further mechanistic and pharmacokinetic studies are underway ( 136 , 137 ).…”
Section: Pseudomonas Exotoxin Amentioning
confidence: 99%
“…PEGylation is a practical and effective strategy to improve the half-life of protein drugs in vivo [ 34 , 35 ]. However, PEGylation may reduce the cytotoxicity of the conjugates while increasing the half-life, where the degree of influence may be closely related to the molecular weight of the poly(ethylene glycol) (PEG) chain [ 36 , 37 , 38 ]. In addition, the coupling mode of PEG chains and small drug molecules may affect affibody affinity with their targets and then in turn affect the biological activity of the conjugates [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…A molecular weight of <60 kDa can result in a fast renal clearance and a reduced serum half-life and consequently requires repeated or continuous systemic administration in the patient. The attachment of polyethylene glycol (PEGylation) is one method to increase the molecular weight and the plasma half-life of targeted toxins [70].…”
Section: Enhancing Tumor Penetration and Affinitymentioning
confidence: 99%